Variability in the nutraceutical properties of fenugreek (Trigonella foenum-graecum L.) sedes - Singh, Krishan Pal; Nair, Beena; Jain, Pramod Kumar; Naidu, Ajay Kumar; Paroha, Seema (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2014)
Fenugreek (Trigonella foenum-graecum L.) leaves and seeds have been used extensively for medicinal purposes. Fenugreek seed is known to exhibit anti-diabetic properties and effects such as hypocholesterolaemic, anticancerous and thyroxine-induced hyperglycaemia. The result of the present experiment reveals considerable variability among fenugreek genotypes. They differ in morphology, growth habit, biomass and seed production capability. Chemical constituents of the seed, e.g. polyphenol, phytic acid, saponin, carbohydrate, protein and proximate analysis (moisture %, ash, fiber, Zn, Fe, Mn, and Mg) contents also differed markedly. This variability is most often overlooked or underestimated in clinical trials. Our research suggests that the genetic variability and the genotype by environmental interaction will play a significant role when the crop is used by the nutraceutical industry. Our research results indicate that the variability for important traits in fenugreek have a genetic base, making selection for improved levels of these traits possible. Fenugreek plays a major role to progress towards the exploitation of crop to overcome micronutrient deficiency in human beings. The associated issues to strengthen crop biofortification through fenugreek research and development have been dealt in this piece of research work.